Temporal trends and global burden of ischemic heart disease attributable to non-optimal temperatures from 1990 to 2021: an analysis of the Global Burden of Disease Study 2021 - Chen, Li; Jiang, Yan; Wang, Jingyuan; Wan, Zhenxun; Peng, Ting; Luo, Gang; Liu, Qiuyu; Liu, Mengnan (Frontiers in Public Health, 2025)
BackgroundGlobal climate change has intensified non-optimal temperature impacts on cardiovascular health. Ischemic heart disease (IHD), a leading cause of mortality, is increasingly linked to temperature anomalies driven by climate change, yet their association remains underexplored. Using Global Burden of Disease (GBD) 2021 data, this study analyzes spatiotemporal trends in temperature-attributable IHD burden from 1990 to 2021.MethodsGBD 2021 data on IHD mortality and disability-adjusted life years (DALYs) across 204 countries were analyzed via joinpoint regression. Stratified analyses by age, sex, region, and sociodemographic index (SDI) assessed subpopulation disparities.ResultsIn 2021, non-optimal temperatures were responsible for an absolute burden of 610,000 IHD deaths (95% UI, 459, 000 to 862, 000) and 1.24 million DALYs (95% UI, 915,900 to 1.76 million) globally. While these absolute figures represented increases of 41.8 and 37.8% since 1990, the age-standardized mortality rate (ASMR) and DALY rate (ASDR) actually decreased by 3.18 and 55.91%, respectively, over the same period, indicating that population growth and aging are key drivers of the rising absolute count. When examining the attribution of temperatures, the impact of low temperatures (accounting for 81.8% of the burden) was significantly higher than that of high temperatures (accounting for 18.2% of the burden). Regional disparities persisted, with high-SDI regions experiencing the largest decline in ASMR (6.5%), while low/middle-SDI regions faced rising burdens. The impact of high temperatures grew faster in these vulnerable regions. Males had higher absolute deaths and ASMR than females, and population of older adults were most vulnerable.ConclusionNon-optimal temperatures, particularly rising high-temperature impacts, are critical environmental risks for IHD. The accelerating high-temperature-attributable ASMR over the past decade highlights underestimated risks. Region-specific strategies addressing climatic and demographic vulnerabilities are urgently needed to mitigate future IHD burdens.